2017
DOI: 10.1007/s00125-017-4437-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of glucose regulation in pregnancy after gastric bypass surgery

Abstract: Aims/hypothesis Roux-en-Y gastric bypass (RYGB) surgery is characterised by glycaemic variability. Prospective studies of glucose metabolism in pregnancy after RYGB are not available, therefore this study aimed to evaluate physiological alterations in glucose metabolism in pregnancy following RYGB. Methods Sixty-three pregnant women (25 who underwent RYGB, 19 non-operated obese control women and 19 normal weight control women) were included. Frequently sampled 3 h OGTTs and 1 h IVGTTs were performed between 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 45 publications
2
31
0
3
Order By: Relevance
“…Moreover, increased fetal subcutaneous fat tissue is known to be a consequence of maternal diabetes and was shown to be more closely related with poor glycemic control than neonatal birth weight [16], suggesting that alterations in maternal glucose metabolism after bariatric surgery contribute to our observation of altered fetal subcutaneous fat trajectories. This is also supported by another recent study on women after GB indicating that birthweight percentiles are related to maternal hyperinsulinemia and glucose nadir levels during a 3-h 75 g OGTT [19]. However, although postprandial hypoglycemia during a routinely performed 2 h OGTT was frequently observed in the present study, we failed to identify a clear association with reduced FSCTT.…”
Section: Discussionsupporting
confidence: 83%
“…Moreover, increased fetal subcutaneous fat tissue is known to be a consequence of maternal diabetes and was shown to be more closely related with poor glycemic control than neonatal birth weight [16], suggesting that alterations in maternal glucose metabolism after bariatric surgery contribute to our observation of altered fetal subcutaneous fat trajectories. This is also supported by another recent study on women after GB indicating that birthweight percentiles are related to maternal hyperinsulinemia and glucose nadir levels during a 3-h 75 g OGTT [19]. However, although postprandial hypoglycemia during a routinely performed 2 h OGTT was frequently observed in the present study, we failed to identify a clear association with reduced FSCTT.…”
Section: Discussionsupporting
confidence: 83%
“…Moreover, continuous glucose monitoring during pregnancy revealed that RYGB patients spend over 13 % of their time with blood glucose levels below 60 mg/dl [20]. A possible relation between fetal growth and glycemic dysregulation in mothers after GB surgery was also underlined by our previous study where glucose nadir and insulin response during an OGTT were associated with lower birth weight percentiles as well [17]. The two most common types of bariatric surgery, gastric bypass and gastric banding, seem to affect pregnancy outcomes differently.…”
Section: Discussionmentioning
confidence: 78%
“…3). Bariatric surgery was shown to severely affect glucose metabolism in pregnant and non-pregnant patients [6,17]. Within the last decade, the focus was set on investigating maternal hyperglycemia and its impact on fetal growth due to the rising prevalence of obesity-linked gestational diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the type of bariatric surgery (e.g., RYGB), fast glucose absorption during an OGTT might lead to severe postabsortive hypoglycaemia [ 7 ]. Recent evidence demonstrates difficulties in the interpretation of OGTT results as plasma glucose concentrations after oral glucose load are altered following gastric bypass and characterized by rapidly changing glucose levels as well as high risk for reactive hypoglycaemic events following glucose load [ 34 37 ]. This might lead to misinterpretation of postprandial glucose levels as one-hour levels misleadingly appear too high, and two-hour levels appear too low, and thus, diagnostic alternatives to define impaired glucose tolerance in pregnancies affected by metabolic surgery need to be found.…”
Section: Resultsmentioning
confidence: 99%
“…Due to changes in glucose absorption after bariatric procedures, rapid postprandial plasma glucose increases followed by rapid decreases and risk for dumping syndrome occur in many patients. In pregnant women after RYGB, postprandial hypoglycaemia was reported in nearly 55% up to 90% of women after a 75 g OGTT between 24 and 28 weeks of gestation [ 34 , 37 ]. Furthermore, higher incidence of SGA offspring and associations of postprandial glucose nadir with fetal growth were reported [ 34 , 37 ].…”
Section: Resultsmentioning
confidence: 99%